Skip to main content

Section 4.4 AM/GM Inequality and Cauchy-Schwarz

In this section we cover some very useful inequalities that allow us to separate terms in a product. As a warm-up, let's begin with the following.

Notice that on one side of the above inequality, the terms \(u\) and \(v\) are multiplied together, and on the other side, they are separate (but now squared).

Since\((u-v)^2\geq 0\text{,}\) we get

\begin{equation*} 0\leq (u-v)^2 =u^2-2uv + v^2\text{.} \end{equation*}

So we can add \(2uv\) to both sides to get

\begin{equation*} 2uv \leq u^2+v^2 \end{equation*}

and then we can multiply both sides by \(\frac{1}{2}\) to get \(uv \leq \frac{u^2+v^2}{2}\) as desired.

When does equality hold in the previous lemma? That is, when do we have \(uv = \frac{u^2+v^2}{2}\text{?}\)

Solution.

Let's retrace the proof of Lemma 4.4.1 backwards trying to use only equalities. If \(2uv=u^2+v^2\text{,}\) then

\begin{equation*} 0 = 2+v^2-2uv = (u-v)^{2}\text{,} \end{equation*}

and this last equality holds if and only if \(u=v\text{.}\)

From this, we deduce the famous Arithmetic Mean-Geometric Mean inequality:

That is, the geometric mean on the left is at most the arithmetic mean on the right.

Write \(a = (x_1 + \cdots + x_n)/n\) for the arithmetic mean. First, let us consider the case in which we have \(x_1=\cdots=x_n=a\text{.}\) In that case, we have equality, because both the arithmetic and geometric means are equal to \(a\text{.}\) In particular, the claim is true for \(n=1\text{.}\)

Now for an induction argument, we may assume that the claim holds for \(n=k\text{,}\) where \(k\in\NN\text{,}\) and we aim to prove it for \(n=k+1\text{.}\) Furthermore, we may assume that at least two of the \(x_i\) are unequal to \(a\text{;}\) in particular \(a>0\text{.}\) Since one of these must be larger than \(a\) and the other must be smaller, we are free to assume that \(x_k\lt a\) and \(x_{k+1}\gt a\text{.}\) We aim to show that

\begin{equation*} x_1x_2\cdots x_{k+1} \lt a^{k+1}\text{.} \end{equation*}

If any of the \(x_i\)s are zero, then the geometric mean vanishes, so we have our strict inequality.

Now set \(\xi_k = x_k + x_{k+1}-a\text{;}\) note that \(\xi_k > 0\text{.}\) Now \(a = (x_1+x_2+\cdots +x_{k-1}+\xi_k)/k\text{.}\) So by hypothesis, we have

\begin{equation*} x_1x_2\cdots x_{k-1}\xi_k \leq a^k\text{,} \end{equation*}

with equality if and only if \(x_1=x_2=\cdots=x_{k-1}=\xi_k\text{.}\) Now note that

\begin{equation*} 0 \lt (a-x_k)(x_{k+1}-a) = (x_k + x_{k+1}-a)a - x_kx_{k+1} = \xi_ka-x_kx_{k+1}\text{,} \end{equation*}

so we deduce that

\begin{equation*} x_1x_2\cdots x_{k-1}x_kx_{k+1} \lt x_1x_2\cdots x_{k-1}\xi_ka \leq a^ka = a^{k+1}\text{,} \end{equation*}

as desired.

The next useful inequality is the Cauchy-Schwarz inequality:

Let \(a=\sqrt{x_1^2+\cdots+x_n^2}\text{,}\) and let \(b=\sqrt{y_1^2+\cdots+y_n^2}\text{.}\) We aim to show that

\begin{equation*} \frac{x_1y_1}{ab}+\cdots+\frac{x_ny_n}{ab} \leq 1 \end{equation*}

Now by the AM/GM Inequality, we have, for each \(i\text{,}\)

\begin{equation*} \frac{x_iy_i}{ab} \leq \frac{1}{2}\left(\frac{x_i^2}{a^2}+\frac{y_i^2}{b^2}\right)\text{.} \end{equation*}

Now if we sum these over all \(i\text{,}\) the right hand side becomes

\begin{equation*} \frac{1}{2}\left(\frac{x_1^2}{a^2}+\frac{y_1^2}{b^2}\right)+\cdots+\frac{1}{2}\left(\frac{x_n^2}{a^2}+\frac{y_n^2}{b^2}\right) = \frac{1}{2}\left(\frac{x_1^2+\cdots+x_n^2}{a^2}+\frac{y_1^2+\cdots+y_n^2}{b^2}\right) = 1\text{,} \end{equation*}

and so the proof is complete.

Why is this useful? On the left we have a mixed product of \(x\)-terms and \(y\)-terms, and we are able to relate it to a product of two terms where now the \(x\)'s and \(y\)'s are separated.

Show that

\begin{equation*} \frac{a+b}{2} \leq \left(\frac{a^2+b^2}{2}\right)^{\frac{1}{2}}\text{.} \end{equation*}

Which of our above inequalities should we try using? Lemma 4.4.1 and AM-GM don't seem relevant since we don't have something like \(ab\) on the left, so let's see if we can use the Cauchy-Schwarz inequality: Rewrite \(\frac{a+b}{2}=a\cdot \frac{1}{2} +b\cdot\frac{1}{2}\text{,}\) then the Cauchy Schwarz inequality implies:

\begin{equation*} \frac{a+b}{2} = a\cdot\frac{1}{2} + b\cdot\frac{1}{2} \leq \sqrt{a^2+b^2}\sqrt{\frac{1}{2^{2}}+\frac{1}{2^{2}}} =\left(\frac{a^2+b^2}{2}\right)^{\frac{1}{2}}\text{.} \end{equation*}